FAW-Volkswagen Audi : leader (1987-2000) - McFarlan, F. Warren (SAGE Knowledge. Cases., 2016)
The FAW-Volkswagen Audi "trilogy" case describes Audi's development history in China and the problems it faces currently, as well as demonstrating the strategies employed by FAW-Volkswagen Audi in their thirty year business partnership. The case illustrates the difficulties faced by Audi and FAW in setting up a supply chain and how the different companies resolved their conflicting cultures to quality to become profitable and mass produce cars.